Glu298Asp, -786T>C, and Intron 4 a/b Polymorphisms of Endothelial Nitric Oxide Synthase Gene in Behçet’s Disease - Remin AKÇAY TAN; Halil Gürhan KARABULUT; Ayşe BOYVAT; Işık BÖKESOY2 (Archives of Rheumatology, 2011)
Objectives: In this study, we investigated the relationship between endothelial nitric oxide synthase (eNOS) gene polymorphisms and predisposition to Behçet’s disease. Patients and methods: One hundred and fifty-five unrelated patients (69 males, 86 females; mean age 40.5 years; range 14 to 66 years) and 98 healthy controls (43 males, 55 females; mean age 34.2 years; range 17 to 78 years) were examined for eNOS gene Glu298Asp, -786T>C and intron 4 a/b polymorphisms. Results: The GG genotype in the Glu298Asp polymorphism was found to be significantly higher in the patient group (p=0.02). The TT genotype in the -789T>C polymorphism was found to be more prevalent in the control group (p<0.001). The distribution of the intron 4 a/b polymorphism and allele frequencies did not differ significantly between the two groups. Conclusion: In our study, the -786T>C polymorphism was found to be correlated with Behçet’s disease, irrespective of family history, age at onset of the disease, or clinical findings. The C allele was found to be more prevalent in patients with Behçet’s disease. The intron 4 a/b and Glu298Asp polymorphisms were not found to be directly related to the disease.